The Quantitative Grammar and Poetics of Finite Verb Forms in the GuslÊ¹ Dobroglasnaia by Simeon Polotsky - Dviniatin, Fedor N. (SlovÄ›ne = Ð¡Ð»Ð¾Ð²Ñ£Ð½Ðµ. International Journal of Slavic Studies, 2015)
The paper offers data on the quantity and structure of finite verbal forms in Simeon Polotskyâ€™s collection GuslÊ¹ Dobroglasnaia. The results are compared to data from twenty epinician odes by Mikhail Lomonosov and ten odes by Gavriil Derzhavin. We find 851 personal forms in Simeonâ€™s collection, of which 214 belong to past tenses (73 to imperfect, 92 to aorist, 49 to past tense with l morpheme); 363 belong to present tense; 99 to future tense; 51 to imperative mood; 6 to conjunctive mood; and 118 to the forms with the da particle. The total percentage of past tenses in Simeonâ€™s texts (25.1%) is close to the parameters appearing in Lomonosovâ€™s and Derzhavinâ€™s texts (21.4% and 23.5%, respectively), and the same is true for the percentages of non-indicative moods (20.5% vs. 19.1% and 20.5%). Simeon Polotskyâ€™s texts contain fewer present tense forms than those written by the 18th-century poets (42.8% vs. 50.6% and 49.5%), but they contain more future tense forms (11.6% vs. 8.9% and 6.5%). Past tense forms in Simeonâ€™s texts with l suffix include 29 forms of the third person with the auxiliary iestÊ¹ verb, usually given in a rhyme position. In the aorist, the proportion of imperfective and perfective forms to the forms of the byti verb is 9:72:11; in imperfect, this proportion is 52:6:15; and in past tenses with l suffix, it is 8:38:3. We find 99 forms of the future tense, broken down as follows: 69 are forms of simple future; 12 are accompanied by imatÊ¹ and similar forms; and 18 are accompanied by budet and similar forms (there is no semantic difference between these two last cases). Of the forms containing the da particle, 65 belong to present tense, 37 belong to future tense, and 16 are accompanied by byti forms. Ð’ ÑÑ‚Ð°Ñ‚ÑŒÐµ Ð¿Ñ€Ð¸Ð²Ð¾Ð´ÑÑ‚ÑÑ Ð´Ð°Ð½Ð½Ñ‹Ðµ Ð¾ ÐºÐ¾Ð»Ð¸Ñ‡ÐµÑÑ‚Ð²Ðµ Ð¸ ÑÐ¾ÑÑ‚Ð°Ð²Ðµ Ð»Ð¸Ñ‡Ð½Ñ‹Ñ… Ñ„Ð¾Ñ€Ð¼ Ð³Ð»Ð°Ð³Ð¾Ð»Ð° Ð² â€œÐ“ÑƒÑÐ»Ð¸ Ð´Ð¾Ð±Ñ€Ð¾Ð³Ð»Ð°ÑÐ½Ð¾Ð¹â€ Ð¡Ð¸Ð¼ÐµÐ¾Ð½Ð° ÐŸÐ¾Ð»Ð¾Ñ†ÐºÐ¾Ð³Ð¾. Ð ÐµÐ·ÑƒÐ»ÑŒÑ‚Ð°Ñ‚Ñ‹ ÑÑ€Ð°Ð²Ð½Ð¸Ð²Ð°ÑŽÑ‚ÑÑ Ñ Ð¿Ð¾Ð´ÑÑ‡ÐµÑ‚Ð°Ð¼Ð¸ Ð¿Ð¾ 20 ...